PENYELESAIAN SENGKETA MELALUI SMALL CLAIM COURT - Sari, Septi Wulan (Ahkam: Jurnal Hukum Islam, 2016)
Small Claims Court is a court which is informal, simple and low-cost, has the force of law, and is intended to provide a quick and economical solution to resolve disputes which does not require an expensive cost. This research is a Library Research or literature review that includes: the systematic identification, analysis of documents containing information related to the problems of the study. The approach used in this study is normative juridical approach. In the developed countries which follow SCC Systems Common Law and Civil Law systems, such approach has become one of the alternatives that are used in the handling of cases in the state. In Indonesia the problem of the Small Claims Court is described in PERMA No. 2/2015. Kata kunci: Penyelesaian Sengketa, Sengketa Sederhana, Small Claim Court